Minimum wages in monopsonistic labor markets - Luis Felipe Munguia Corella (IZA Journal of Labor Economics, 2020)
Over the last 30 years, researchers have disputed the mixed evidence of the effect of the minimum wage on teenage employment in the United States. Whenever the minimum wage has positive or no effects on employment, they appeal to monopsony models to explain their results. However, very few of these studies have empirically tested whether their results are due to monopsonistic characteristics in the labor markets. In this article, I estimate the effects of the minimum wage for the United States under concentrated labor markets and low-mobility jobs (two variables that measure monopsony), identify heterogeneous effects among different scenarios derived from the monopsony model, and provide a plausible explanation of the mixed results about the minimum wage effects in the literature. My main findings indicate that minimum wages have an elasticity to teenage employment of -0.418 under perfect competition, which is, as expected, much higher than the usual results in the literature. If the monopsony variable is one standard deviation higher than the baseline, it implies a positive change in elasticity of 0.05. The minimum wage has a positive insignificant effect between 0.04 and 0.29 under full monopsonistic labor markets. The results are consistent among different specifications and in controlling for possible external shocks and omitted variables.
Keywords: J01; J08; J42; J48; J38; 330; minimum wage; monopsony; labor policy; oligopsony